2020
DOI: 10.1021/acsomega.0c03297
|View full text |Cite
|
Sign up to set email alerts
|

On the Crystallization of Hydroxyapatite under Hydrothermal Conditions: Role of Sebacic Acid as an Additive

Abstract: Hydroxyapatite (HAp) is a major inorganic component in bone minerals and is often used for bone tissue engineering. Herein, we synthesized HAp using sebacic acid as an additive at different pH values by a hydrothermal method. Sebacic acid, which has two carboxyl group ends of the carbonate chain, binds with Ca ions during the hydrothermal process to become a crystal nucleation site in (001) and at the same time could act as an inhibitor in a specific direction [i.e., (110)] for the HAp crystal growth. Sebacic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(34 citation statements)
references
References 48 publications
3
30
1
Order By: Relevance
“…However, the morphology of HA particles changed from spherical to flower-like and rod-like. Furthermore, irregular HA particles were deposited on the scaffolds when the pH value of the reaction solution was at 4 or 10, suggesting that the weakly acidic or alkaline environment of the original reaction solution facilitates to form regular HA particles, which was similar to other reported study [32]. On the other hand, the M 2 S-HA scaffolds were ultrasonically treated in deionized water bath for 30 s and rinsed with ethanol, and SEM observation confirmed that the deposited HA particles have not been dropped off from the scaffolds, suggesting that HA particles could stably bond to the surface of the scaffolds.…”
Section: Resultssupporting
confidence: 88%
“…However, the morphology of HA particles changed from spherical to flower-like and rod-like. Furthermore, irregular HA particles were deposited on the scaffolds when the pH value of the reaction solution was at 4 or 10, suggesting that the weakly acidic or alkaline environment of the original reaction solution facilitates to form regular HA particles, which was similar to other reported study [32]. On the other hand, the M 2 S-HA scaffolds were ultrasonically treated in deionized water bath for 30 s and rinsed with ethanol, and SEM observation confirmed that the deposited HA particles have not been dropped off from the scaffolds, suggesting that HA particles could stably bond to the surface of the scaffolds.…”
Section: Resultssupporting
confidence: 88%
“…The revealed characteristic planes of NX-HAPs (410), (510), (400) and MB-NX-HAPs (002), (004), (510) represented the planes of hydroxyapatite as reported earlier (Figure S3B,C). The high-resolution TEM (HRTEM) suggested lattice spacings of 0.30 and 0.27 nm for NX-HAPs (Figure S3D) and MB-NX-HAPs (Figure S3E), respectively, corresponding to (210) and (300) planes of hydroxyapatite nanomaterial . Additionally, the energy-dispersive X-ray (EDX) spectroscopy investigation displayed the elemental composition of the as-synthesized NX-HAPs and MB-NX-HAPs (Figure S4A,B).…”
Section: Resultsmentioning
confidence: 98%
“…The high-resolution TEM (HRTEM) suggested lattice spacings of 0.30 and 0.27 nm for NX-HAPs (Figure S3D) and MB-NX-HAPs (Figure S3E), respectively, corresponding to (210) and (300) planes of hydroxyapatite nanomaterial. 37 Additionally, the energy-dispersive X-ray (EDX) spectroscopy investigation displayed the elemental composition of the as-synthesized NX-HAPs and MB-NX-HAPs (Figure S4A,B). Moreover, characterization using FESEM conveyed the size of NX-HAPs to be 67.5 ± 6.4 nm and that of MB-NX-HAPs to be 60.5 ± 3.5 nm, in support of the TEM data obtained (Figure S5A,B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The Fourier transform infrared (FT-IR) spectra of the synthesized HAP·CeO 2 (HC), HAP·CeO 2 ·La­(OH) 3 (2:1) (HCL 1), and HAP·CeO 2 ·La­(OH) 3 (3:2) (HCL 2), given in Figure , show broad peaks at 1631, 1625, and 1619 cm –1 , respectively, which indicate the presence of the OH group in adsorbed water. The peaks at 603 and 563 cm –1 of the HCL 2 spectrum and at 602 and 561 cm –1 of the HC and HCL 1 spectra refer to the bending mode of the phosphate (O–P–O) group. ,, Moreover, the adsorption bands that appeared in the range of 1027–1030 and 1100–1104 cm –1 represent the asymmetrical and symmetrical stretching modes of P–O and phosphate. , In addition, a duplex peak appeared at 1489 and 1379 cm –1 of HCL 1, which refers to the carbonate peak, which resulted due to the CO 2 adsorption by HAP . The band that appeared in the 450–550 cm –1 region can be assigned to the Ce–O stretching vibration. Moreover, the adsorption peak observed in the 652 cm –1 region in the HCL 2 spectrum and the small peak that appeared in the 637 cm –1 region of the HCL 1 spectrum represent the vibrational mode of the La–O bond .…”
Section: Results and Discussionmentioning
confidence: 99%